Surface Properties of Synthetic Calcium Hydroxyapatite - N.V. Nikolenko; E.E. Esajenko (Adsorption Science & Technology)
The composition of the adsorption centres of hydrated calcium hydroxyapatite was studied. It was found that the adsorption of organic bases was due to the formation of surface hydrogen bonds between their nitrogen atoms and the ≡POH groups of hydroxyapatite. Aromatic acids and alcohols were adsorbed in an ionic form due to the formation of intraspheric complexes with surface Ca 2+ cations. It was concluded that the adsorbability of organic compounds depends on the relationship between the greatest effective charges on their atoms and the atoms of water molecules.